Kajian Perilaku Penurunan Bangunan Tinggi: Studi Kasus dan Analisis - Dani, Hanny Juliany (Universitas Kristen Maranatha, 2025)
The main problem in the construction of high-rise buildings is land subsidence which can affect the stability and safety of the structure. This study aims to analyze the behavior of the settlement of high-rise buildings based on various case studies in several locations, such as Chicago, Frankfurt, Shanghai, Singapore, Jakarta, and Surabaya. The analysis was carried out by comparing the results of theoretical predictions obtained through analytical calculations and finite element methods (FEM) with the data of measurement results in the field. The study also evaluated the factors that affect the magnitude of the settlement, including soil characteristics, structural loads, and the foundations used. The choice of foundation is one of the important factors. In overconsolidated clay soil, the largest settlement occurred was the settlement until the end of the construction period (initial settlement). The settlement that occurs can reach around 40-70% of the total settlement, some even reach 90%. For soils that have high rigidity, the use of raft foundations for tall buildings can be recommended. In Surabaya, the actual settlement (3.5 cm) was smaller than the theoretical prediction (13 cm) and FEM (15 cm), the mismatch reaching 77% was suspected to be due to expansive soil pressure swelling that was not detected in the model.